ANALISIS STRATEGI PENGELOLAAN WISATA ALAM TAMAN TIRTASARI SONGSANG, KABUPATEN AGAM - Ahin Nainggolan; Zuwardi (CV. Adiba Aisha Amira, 2023)
The management of tourism activities is very important to be carried out on an object because it is a change in the conditions that are applied. If you do not manage a tourist object, there will be no developments and changes that occur to the object. With good and correct management of the tourism sector, the tourism sector can create jobs, business opportunities for the community and can drive the local and regional economy. However, the management of the Tirtasari Songsang Park tourism area does not optimize the existing attractions. The research method used in this study is a qualitative descriptive approach. Data collection techniques by observing, interviewing, and documentation. The informants in this study were the managers of the Tirtasari Songsang Park tourist attraction, the public, and visitors to the Tirtasari Songsang Park tourist attraction. The method of analysis in this study is to use SWOT analysis to analyze the strengths, weaknesses, opportunities and threats in tourism development in Taman Tirta Sari Songsang. Based on the results of the research, it shows that tourism management in the Tirtasari Songsang Park has not been carried out optimally and still requires great attention from the manager. By using the SWOT analysis for tourism management, a suitable strategy is to use the S-O (Strengh-Opportunity) strategy, which is to use the strengths you have to take advantage of existing opportunities: 1. By reason of the many opportunities that can be utilized in tourism management, 2. Improvements in the facilities and infrastructure sector to attract visitors, 3. Development of tourism potential by maintaining existing potential.